Kajian Nilai Budaya Pendidikan Olahraga dalam Permainan ‘Pasola’ di Tanah Marapu Kabupaten Sumba Barat Daya Nusa Tenggara Timur - Dionesius Wora; Timoteus Ajito; Mansuetus Mola (Departement of Mathematics Education, 2023)
One of the cultural heritages of the Indonesian nation is the tradition of the pasola game. Besides loaded with a variety of skills and agility to defend themselves. Pasola is also to test virility, courage between youths in Southwest Sumba district which is rich with the traditions that surround it. Pasola sports are very rich in socio-cultural values and philosophical meanings. This study aims to find out, 1) What are the noble values in the Pasola game for the people of Southwest Sumba, 2) How is the implementation of the Cultural Values of Sports Education in the Pasola game in Southwest Sumba district and 3) What is the role of traditional leaders in carrying out the Pasola game process in Tanah Marapu, Southwest Sumba Regency, and saw the process of inheriting the Pasola sport from generation to generation. This study uses a qualitative approach where data is obtained using Miles Matthew's analysis. B and Huberman Michael, which consists of three stages, namely data reduction, data presentation, and ends with drawing conclusions. The results of the study show that the Pasola game is not just a sport, but is full of value and meaning in people's lives. The process of inheriting Pasola has also been going well so far.